Membracidae diversity (Hemiptera: Auchenorrhyncha) in an Atlantic Forest area, Paraíba, Brazil, with preliminary comments on collection methods, spatial distribution and estimated species richness - Creão-Duarte, Antonio José; Pereira-Colavite, Alessandre; dos Santos, Wellington Emanuel; Barbosa, Suênia Alcântara; Cabral, Valberta Alves; Lourenço, Aline; Braga, Izabela Souza; da Silva, Wylma Regina (Boletim do Museu Paraense Emílio Goeldi - Ciências Naturais, 2017)
In order to document the Membracidae of an area of the Brazilian Atlantic Forest in Paraíba, four collection methods were employed, distributed in 100 sample units during ten days in November 2014. A total of 1,182 membracids of 27 species were collected. The assemblages were marked with a high dominance, since six species accounted for 80.63% of the total number of individuals captured. Species with more than ten individuals were associated with the three environments of the forest: canopy, understory, and edge. The importance of the four sampling methods in the final membracid composition was evaluated through the Jaccard similarity index and its complement, where the values of complementarity were superior to the values of similarity, suggesting the dissimilarity of assemblages inventoried by each method. The observed richness corresponds to 90.0% and 79.4% of the richness estimated by Chao1 and Chao2. The richness estimated by Chao1 is within the upper limit of the confidence interval (95%) in the last plot of the species accumulation curve, while the richness estimated by Chao2 is above this limit. The additional sampling effort needed to collect 95% of the estimated richness is 969 individuals for Chao1 and 317 sample units for Chao2.